2008
DOI: 10.1109/tro.2007.909786
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Vertical Surface Climbing With Directional Adhesion

Abstract: Stickybot is a bioinspired robot that climbs smooth vertical surfaces such as glass, plastic, and ceramic tile at 4 cm/s. The robot employs several design principles adapted from the gecko including a hierarchy of compliant structures, directional adhesion, and control of tangential contact forces to achieve control of adhesion. We describe the design and fabrication methods used to create underactuated, multimaterial structures that conform to surfaces over a range of length scales from centimeters to microme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 490 publications
(135 citation statements)
references
References 34 publications
1
123
0
Order By: Relevance
“…The performance of various tip shapes was characterized in previous work [34], showing that the mushroom shape enhances adhesion by several fold over a flat tip shape. Finally, anisotropic microstructures use the directional preference of the adhesive's shape, similar to the structures on a gecko toe, to turn adhesion on and off easily [35][36][37].…”
Section: Directional Dry Adhesivesmentioning
confidence: 99%
“…The performance of various tip shapes was characterized in previous work [34], showing that the mushroom shape enhances adhesion by several fold over a flat tip shape. Finally, anisotropic microstructures use the directional preference of the adhesive's shape, similar to the structures on a gecko toe, to turn adhesion on and off easily [35][36][37].…”
Section: Directional Dry Adhesivesmentioning
confidence: 99%
“…When loaded in forward direction, gecko's adhesive toe pads stick with a strong force to the surface, however, they can also be easily peeled off from the surface when loaded in the reverse direction [6]. This directional or anisotropic adhesive behaviour that allows smart or controllable surface attachment and detachment has inspired many applications such as climbing robots [7], clean transportation systems [8,9] and micro-transfer printing mechanisms [10]. Rapid switching of the gecko's toe pads between attachment and detachment can be attributed to millions of inclined seta shafts and to the corresponding loading response of the toes of the gecko [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The shape of the claw is suitable for capturing small objects (Figure 7A), but not for big ones (Figure 7B), and the claw does not create enough friction to hold an object of any significant weight. Therefore, a polymer pad with spines, inspired by the Gecko pad (Kim et al, 2008), was added to the claw, as shown in Figure 7D. The polymer pads were molded from a laser-cut acrylic plate.…”
Section: Adaptive Caging Grippermentioning
confidence: 99%